Impact of Expansion of Vascular Access Team on Central-line–Associated Bloodstream Infections. (October 2020) - Holder, Carolyn; Overton, Elizabeth; Kalaf, Sarah; Wong, Doris; Holdsworh, Jill; Yun, Mylinh; Schreck, Debra; Haun, Philip; Omess, Sarah; Whitson, Margaret; Ott, Deborah; Mitchell, Rae; et al.
Abstract : Background: Through participation in a system-wide healthcare-associated infection-reduction task force, we leveraged our ability to standardize best practices across hospitals in a university-owned healthcare system to reduce central-line–associated bloodstream infection (CLABSI) rates. Methods: Our multidisciplinary team had representation from all hospitals in our healthcare system. The team benchmarked practices in place and compared CLABSI standardized infection ratios (SIRs). One hospital had a robust vascular access team (VAT) and consistently low CLABSI SIRs; expanding and standardizing VAT across the hospitals in the system became the primary goal of the team. We developed a business case to justify VAT expansion that considered savings from decreasing CLABSIs and benefits to interventional radiology revenue by decreasing PICC insertion and comparing costs for added full-time equivalents (FTEs). CLABSI rates before and after VAT team expansion at 2 large hospitals were compared to the hospital with existing robust VAT. Other process improvement activities were implemented across all hospitals. The expanded VAT assumed responsibility for central-line maintenance, promoted removal of unneeded lines, expanded education efforts, and enhanced capacity for insertions. Results: The VAT expansion from 5.4 FTEs to 15.9 FTEs at 2 large hospitals (1, 100 total beds) began in April 2017 and was phased over ~6 months. CLABSI SIRs for the 15 months preceding expansion were compared to the SIRs for the 15-month period after expansion for the 2 hospitals with expanded VAT (hospitals A and B) and for hospital C with preexisting robust VAT (Table 1). We observed a 33% decrease in PICC insertions in interventional radiology department in hospitals A and B. Overall return on investment (ROI) estimates using lower and upper cost per CLABSI ranged from a loss of $156, 000 to a net gain of $623, 000. Conclusions: A significant decrease in CLABSI rates temporally related to expansion of VAT occurred in 2 hospitals, whereas the hospital with existing robust VAT demonstrated a modest decrease in CLABSI rates. We were able to demonstrate a favorable ROI from the VAT expansion without an impact on HAC penalties. Using the model of standardizing best practices across a system and creative ROIs may help justify the addition of scarce resources. Funding: None Disclosures: None